Financing sustainable small-scale forestry: policy issues and lessons from developing national forest financing strategies in Latin America - Boscolo, M.; Dijk, K. van; Savenije, H.H.G. (Center for International Forestry Research, 2010)
Increasing forest financing requires better communication and understanding between the forestry and finance sectors. This can take the form of joint development of financing strategies, instruments and business cases. Limited forest financing is often less about money availability than about poor access. In tapping into new sources of finance (including domestic ones) and realising the potential of new emerging instruments (capital market instruments, payments for environmental services, risk mitigation schemes, guarantees), governance and institutions in both sectors are often a more serious limitation and risk factor than the lack of money. Forest financing mechanisms for small-scale forestry need participatory diagnosis and flexible design in order to respond to diverse—formal and informal— local realities and build on existing livelihood strategies.